Does T Helper Differentiation Correlate with Resistance or Susceptibility to Infection with L. major? Some Insights From the Murine Model - Tacchini-Cottier, Fabienne; Weinkopff, Tiffany; Launois, Pascal (Frontiers in Immunology, 2012)
The murine model of Leishmania major infection has been an invaluable tool in understanding T helper differentiation in vivo. The initial evidence for a role of distinct CD4+ T helper subsets in the outcome of infection was first obtained with this experimental model. The development of CD4+ Th1 cells was associated with resolution of the lesion, control of parasite replication, and resistance to re-infection in most of the mouse strains investigated (i.e., C57BL/6). In contrast, differentiation of CD4+ Th2 cells correlated with the development of unhealing lesions, and failure to control parasite load in a few strains (i.e., BALB/c). Since these first reports, an incredible amount of effort has been devoted to understanding the various parameters involved in the differentiation of these, and more recently discovered T helper subsets such as Th17 and T regulatory cells. The discovery of cross-talk between T helper subsets, as well as their plasticity force us to reevaluate the events driving a protective/deleterious T helper immune response following infection with L. major in mice. In this review, we describe the individual contributions of each of these CD4+ T helper subsets following L. major inoculation, emphasizing recent advances in the field, such as the impact of different substrains of L. major on the pathogenesis of disease.